B-Cell Depletion Improves Islet Allograft Survival with Anti-CD45RB. Issue 1 (February 2014) - Lee, Kang Mi; Yeh, Heidi; Zhao, Gaoping; Wei, Lingling; O'connor, Matthew; Stott, Ryan T.; Soohoo, Julie; Dunussi, Kyri; Fiorina, Paolo; Deng, Shaoping; Markmann, James F.; Kim, James I.
A short course of anti-CD45RB leads to long-term islet allograft survival and donor-specific tolerance in approximately half of immunocompetent mice. We have previously demonstrated that anti-CD45RB antibody-mediated tolerance requires B-cells for cardiac allograft survival. We therefore asked whether B-cells were also required for anti-CD45RB antibody-mediated survival of islets. Unexpectedly, we found that nearly 100% of islet allografts survive long term in B-cell-deficient mice. Similarly, B-cell depletion by anti-CD22/cal augmented anti-CD45RB-mediated tolerance when administered pretransplant, although it had no effect on tolerance induction when administered posttransplant. Our results demonstrate that the role of B-cells in promoting tolerance with anti-CD45RB is graft specific, promoting tolerance in cardiac grafts but resisting tolerance in islet transplantation. These findings may help elucidate the varied action of B-cells in promoting tolerance versus rejection.